Techniques in Coloproctology - Brown, Steven; Gagliardi, Giuseppe; Nelson, Rick.; Lund, Jonathan; Perez, Rodrigo; Perez, Rodrigo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Techniques in Coloproctology is an international journal fully devoted to diagnostic and operative procedures carried out in the management of colorectal diseases. Imaging, clinical physiology, laparoscopy, open abdominal surgery and proctoperineology are the main topics covered by the journal. Reviews, original articles, technical notes and short communications with many detailed illustrations render this publication indispensable for coloproctologists and related specialists. Both surgeons and gastroenterologists are represented on the distinguished Editorial Board, together with pathologists, radiologists and basic scientists from all over the world. The journal is strongly recommended to those who wish to be updated on recent developments in the field, and improve the standards of their work. Manuscripts submitted for publication must contain a statement to the effect that all human studies have been reviewed by the appropriate ethics committee and have therefore been performed in accordance with the ethical standards laid down in an appropriate version of the 1965 Declaration of Helsinki. It should also be stated clearly in the text that all persons gave their informed consent prior to their inclusion in the study. Details that might disclose the identity of the subjects under study should be omitted. Reports of animal experiments must state that the Principles of Laboratory Animal Care (NIH publication no. 86-23 revised 1985) were followed as were applicable national laws (e.g. the current version of the German Law on the Protection of Animals). The Editor-in-Chief reserves the right to reject manuscripts that do not comply with the above-mentioned requirements. Authors will be held responsible for false statements or for failure to fulfill such requirements. The journal is open for publication of supplements and for publishing abstracts of scientific meetings. Conditions can be obtained from the Editor-in-Chief or the publisher.
Keywords: Surgery; Gastroenterology; Proctology; Surgery; Colon (Anatomy)$1 (BSurgery.s; Surgery; Gastroenterology; Proctology; General Surgery; Colorectal Surgery